Protein requirement and efficiency of utilization for maintenance and milk production - RAJAGOPAL, S; TIWARI, S P; MISHRA, U K (The Indian Journal of Animal Sciences, 2013)
Nitrogen balance studies were carried out with 9 each of Sahiwal and Brown Swiss (BS) x Sahiwal (S) crossbred lactating cows in their early stages oflactation under 2 different feeding regimes. The maintenance requirements were 4.1 and 3.97 g / kg w0 75 day for Sahiwal and crossbred cows respectively. The amount of digestible nitrogen required for producing 100g of milk N was 362.9 and 357.2 g. respectively, for Sahiwal and BS x Sahiwal crossbred cows. The over all efficiency of utilization of digestible N for milk production in Sahiwal cows and BS x Sahiwal lactating cows was observed to be 28.1 and 28.6% respectively.